MENULIS KARANGAN NARASI SEBAGAI WADAH MENGEMBANGKAN BERPIKIR KREATIF - Silvia Sandi Wisuda Lubis (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
Writing skills are indirect communication activities or often called nonverbal communication tools, writing has the same meaning as composing, such as writing narrative essays. Wiriting activities require a process of thinking and imagining to be able to convey what is meant to the reader. The activity of writing narrative essays has become a topic of discussion in Indonesian subjects to be studied and is useful for developing writing skills. Narrative essays whose sources of development are through things that are closely related to every day life encountered in yhe surrounding environment can provide many ideas for developing them into writing. Creative ability is generally understood as creativity. Often, the individual who is considered creative is a genuinely good synthetic thinker who builds connections between things that other people don’t notice spontaneously. A creative attitude is at least as important as creative thinking skills. Creativity is relative. This study uses a qualitative research approach where qualitative research as a scientific method is often used and carried out by a group of researchers in the social sciences, including education sciences. The data were analyzed using the percentage formula. The results showed that the percentage of students writing narrative essays was 94.59 % very well and students had completed classically.